Pembelajaran Matematika pada Kurikulum Merdeka dalam Mempersiapkan Peserta Didik di Era Society 5.0 - Ummu Soim Daimah; Suparni . (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2023)
Abstract In the era of society 5.0, technology is developing very rapidly, demanding the availability of quality human resources and being able to answer the challenges of the times. In this case education plays an important role in preparing quality human resources, one of which is in learning mathematics. To support good education, the Minister of Education and Culture issued a policy for the independent learning program. This study aims to determine the learning of mathematics in the independent learning curriculum in preparing students' competencies to be able to compete in the era of society 5.0. This research uses the method of library research or library research. The results of this study are that learning mathematics is relevant to the independent learning curriculum program in the era of society 5.0 which can be seen from learning that focuses on student independence in understanding material. In addition, learning mathematics in the independent curriculum can be a solution for the world of education in facing progress in various fields, especially in the era of society 5.0. This is because the goals in the independent curriculum train students in developing soft skills such as leadership, integrity, communication skills, and good teamwork, as well as forming characters that are in accordance with the profile of Pancasila students so that they can give birth to quality human resources who are able to compete in era of society 5.0. Keyword: Independent Curriculum, Learning Mathematics, Era Society 5.0 Abstrak Pada era society 5.0 teknologi yang berkembang sangat pesat menuntut ketersediaannya sumber daya manusia yang berkualitas dan mampu menjawab tantangan zaman. Dalam hal ini pendidikan berperan penting untuk menyiapkan sumber daya manusia yang berkualitas, salah satunya pada pembelajaran matematika. Untuk mendukung pendidikan yang baik Menteri Pendidikan dan Kebudayaan mengeluarkan kebijakan program merdeka belajar. Penelitian ini bertujuan untuk mengetahui pembelajaran matematika pada kurikulum merdeka belajar dalam mempersiapkan kompetensi peserta didik agar mampu bersaing di era society 5.0. Penelitian ini menggunakan metode studi pustaka atau library research. Hasil dari penelitian ini adalah pembelajaran matematika relevan dengan program kurikulum merdeka belajar di era society 5.0 yang dapat dilihat dari pembelajaran yang terfokus pada kemandirian siswa dalam memahami materi. Selain itu, pembelajaran matematika pada kurikulum merdeka dapat menjadi solusi bagi dunia pendidikan dalam menghadapi kemajuan di berbagai bidang khususnya pada era society 5.0. Hal ini dikarenakan tujuan dalam kurikulum merdeka melatih peserta didik dalam mengembangkan soft skill seperti kepemimpinan, integritas, keterampilan komunikasi, dan kerja sama tim yang baik, serta membentuk karakter yang sesuai dengan profil pelajar pancasila sehingga dapat melahirkan sumber daya manusia yang berkualitas yang mampu bersaing di era society 5.0. Kata Kunci: Kurikulum Merdeka, Pembelajaran Matematika, Era Society 5.0